Kajian Penggaraman dan Pengeringan Belimbing Wuluh (Averrhoa bilimbi L.) Dalam Pembuatan Asam Sunti Dari Aceh - Ria Hayati; Soewarno Soewarno; T. Soekarto; Lilis Nuraida (Agricultural Faculty, 2002)
ABSTRACT.Asam sunti is a popular traditional product commonly used as a condiment in Aceh. It is a fermented and popular product, wich has an important economic role in Aceh rural community. However, this traditional dried condiment is mostly poor in appearance, calour and keeping qualities. The research is aimed to study curing, drying and fermentation processes for improvement of quality and shelf life of the product. The result indicated that curing by salting prior drying was better than traditional curing by salting after drying. Likewise mechanical drying was also better than traditional sun drying. Both better processes could improve calour, lower mouisture content, lessen sournes and improve shelf life. The chemical composition of the fresh fruits with pH at 2.44 and mouisture content 70.16% in asam sunti with PH at 1.72. Bacterial plate count of the treated as well as the traditional product (as control) revealed very stable product and no bacterial content, wich account of very low PH (1.7) and water activity (0.70 087) condition for bacterial growth.